Serum Albumin as an Early Predictor of Severity in Patients with Acute Pancreatitis - Oscar Francisco Iniestra-Ayllón; José Antonio Morales-González; Karina Sánchez-Reyes; Elda Victoria Rodríguez-Negrete (Gastroenterology Insights)
Acute pancreatitis (AP) is one of the gastrointestinal pathologies that most frequently requires hospital admission; about half of all deaths occur within the first two weeks and are caused by multi-organ failure. Predicting the degree of severity of AP before 48 h is a challenge. Background/Objectives: Having an early marker, before 48 h after admission, could be useful to avoid or diagnose early complications such as organ failure (OF). A few sentences could place the question addressed in a broader context and highlight the purpose of the study. Methods: A retrospective study conducted in a third-level hospital, during the period from August 2019 to June 2021. Patients aged >18 years, with a diagnosis of PA, who had a complete clinical history and complete biochemical and imaging data were included. The scores of the APACHE II, BISAP, revised Atlanta classification, and modified Marshall scales were recorded. Results: Of the 103 patients included, 60% were women, the mean age was 47.76 years, and the hospital stay was 8 days (IQR 6–12); the most frequent etiology was biliary in 46 (44.7%) patients; the most frequent BMI was overweight with 34 (33%) patients; and 38 (36.9%) patients had a systemic inflammatory response at admission. Hypoalbuminemia was observed in 34 (33%) of the 103 patients at admission; of these, 42 (40.8%) had an APACHE II score > 8 points, 17 (16.3%) a BISAP score > 2, 57 (54.8%) patients were classified as moderate AP according to the revised Atlanta classification, and 54 patients had a score according to the modified Marshall score > 2. A statistically significant difference in the development of death was observed between patients with hypoalbuminemia versus those with normal serum albumin levels. Conclusions: In this study, we show the usefulness of hipoalbuminemia (<3.5 g/dL) at hospital admission in patients with AP, as a severity and mortality indicator. With the results obtained, we conclude that low albumin levels are a good predictor of severity and are useful for establishing timely treatment and close follow-up.